Realizing a Democratic Community of Teachers: John Dewey and the Idea of a Science of Education - Jeff Frank (Education Sciences, 2017)
In this paper, I make the case that John Dewey’s philosophy of education aims to bring about a democratic community of teachers capable of creating a science of teaching. To make this case, I will do a three things. First, I will discuss Sources of a Science of Education and argue that this work is deeply connected to a work written at about the same time, Individualism Old and New. As I will show, the creation of a science of education is a complex endeavor that is premised on an ability to create a democratic community that reconstructs outmoded notions of individuality. Second, I will argue that the position put forward most directly in these later works is not a deviation from Dewey’s overall educational philosophy by offering a reading Democracy and Education. I will argue that Dewey’s thinking on a science of education is held nascent within Democracy and Education, especially in his discussion of individualism and democracy. Finally, I will assess whether and how current work in teacher education is consonant with Dewey’s philosophical project, and draw out implications for philosophers of education.